2021
DOI: 10.3390/electronics10020137
|View full text |Cite
|
Sign up to set email alerts
|

Trapping Dynamics in GaN HEMTs for Millimeter-Wave Applications: Measurement-Based Characterization and Technology Comparison

Abstract: Charge trapping effects represent a major challenge in the performance evaluation and the measurement-based compact modeling of modern short-gate-length (i.e., ≤0.15 μm) Gallium Nitride (GaN) high-electron mobility transistors (HEMT) technology for millimeter-wave applications. In this work, we propose a comprehensive experimental methodology based on multi-bias large-signal transient measurements, useful to characterize charge-trapping dynamics in terms of both capture and release mechanisms across the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
(68 reference statements)
1
9
0
Order By: Relevance
“…The simulated LF Y21 parameters, with a good match, illustrate In the literature [8,11,40], it is reported that the surface traps may show a weak dependency on temperature, as their capture/emission kinetics is essentially governed by the hopping conduction mechanism and results in a lower thermal activation energy. In this work, both the measured and simulated Y 21 properties (Figures [15][16][17] show that the carrier emission rate for the surface trap D1 is a thermally activated process, postulating that the trapping/de-trapping dynamics is carried out through the conventional SRH recombination statistics; this observation is important to model the surface-trapping phenomena in the AlGaN/GaN HEMTs.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The simulated LF Y21 parameters, with a good match, illustrate In the literature [8,11,40], it is reported that the surface traps may show a weak dependency on temperature, as their capture/emission kinetics is essentially governed by the hopping conduction mechanism and results in a lower thermal activation energy. In this work, both the measured and simulated Y 21 properties (Figures [15][16][17] show that the carrier emission rate for the surface trap D1 is a thermally activated process, postulating that the trapping/de-trapping dynamics is carried out through the conventional SRH recombination statistics; this observation is important to model the surface-trapping phenomena in the AlGaN/GaN HEMTs.…”
Section: Discussionmentioning
confidence: 74%
“…The drain current transient (DCT) spectroscopy is a powerful tool to examine the temporal evolution of the carrier trapping and de-trapping phenomena in the GaN HEMT [8][9][10][11][12][13][14][15][16][17][18]. Figure 5 depicts the DCT recovery spectra of the AlGaN/GaN HEMT acquired with the drain-lag filling pulse at increasing temperature levels.…”
Section: Measured Dct Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The most evident difference between the GaAs and GaN technologies is that the former is more mature, whereas the latter is more suited for high-power applications, owing to its wide bandgap nature. Over the years, many studies have focused on the high-frequency characterization and modeling of the temperature-dependent behavior of both GaAs [3][4][5][6][7][8][9][10][11][12] and GaN [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] HEMTs. This is because the operating temperature can remarkably affect the device performance, reliability, and lifetime, which are key features in practical applications, especially those in harsh environmental conditions [28].…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades, enormous efforts were put into the development of materials and devices based on group III-nitride heterostructures such as AlGaN/GaN hetero field effect transistor (HFET) as well as well-known high electron mobility transistor structures for solid-state RF power applications [1][2][3][4][5][6][7][8][9][10][11][12][13]. There is no doubt, that current device technologies based on group III-nitrides represent the indispensable milestone in arising 5G wireless communication network architectures [14][15][16][17]. Furthermore, their role in automotive industry especially in power inverters used for electric vehicles is expected to be essential also to further progress [10,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%